Native forest conservation within the framework of forest promotion policy in Uruguay - Normey, Andrés (2012)
Environmental changes due to anthropogenic causes have brought a negative effect on Uruguayan native forest. Governments at the beginning of the 20th century began to promote the importance of the forest. In 1968 was passed the “Resources and Forest Economy Law” and in 1987 was passed the “Forest Law”. Both laws intended to boost afforestation on certain priority areas with exotic species, whilst promoting the conservation of the native forest. This thesis focuses on describing and thoroughly analysing the processes that resulted in the protection of native forest within the framework of the forest promotion legislation during the 1960s and 1980s. The theoretical framework selected was the Policy Arrangement Approach (PAA). It distinguishes four interrelated key variables to understand policy practices: discourses, power, rules and actors. Methods selected relied on qualitative rather than quantitative analysis. They were based on literature analysis (thorough the review of historical documentation) and qualitative interviews with open questions. Four major themes emerged from the analysis. First, there were three main groups of actors responsible for initiating the forest development: politicians in power, national forest promoters and FAO. Second, national forest promoters were identified to be the main force that drove the inclusion of native forest conservation. They lead the General Forest Directorate, the most important organisation which has stood for native forest conservation. Their discourses evolved from simply the importance of enlarging the forest area in the country, to the importance of preserving native forest for soil protection and waters regulation functions. Later on, biodiversity and recreation began to become important for the intrinsic value of native forest. Third, there was no organised opposition to the creation of a forest legal framework. However, some livestock producers had been individually opposed to forest promotion. Fourth, it is important to stress the strong influence of FAO and the regional forest regimes. These were not the main drivers, but the outcome of forest policy in Uruguay would have been different without such influences.